MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN, BERPIKIR KRITIS, DAN BERBICARA MURID MENGGUNAKAN MODEL PEMBELAJARAN BERCERITA DI KELAS V SDN TELAGA BIRU 6 - Nurhapsari, Tiara; Dwitalia Sari, Dessy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low levels of learning activity and deficiencies in reading comprehension, critical thinking, and speaking skills have resulted in suboptimal Indonesian language learning outcomes for fifth-grade students. This study aimed to evaluate the effectiveness of the BERCERITA learning model in enhancing these three skills as well as student learning outcomes, employing a Classroom Action Research (CAR) approach with 14 fifth-grade students from SDN Telaga Biru 6 as participants. Data were collected through observation, interviews, and tests, and subsequently analyzed using both qualitative and quantitative methods. The results demonstrated improvements in reading comprehension and critical thinking skills from 28.6% to 92.8%, and in speaking skills from 14.3% to 92.8%. Mastery of learning outcomes also improved, with achievement rates reaching 100% in the affective and psychomotor domains and 92.8% in the cognitive domain. Thus, the BERCERITA learning model has proven effective as an alternative for enhancing the quality of Indonesian language instruction in primary schools.